Different Neutralization Profiles After Primary SARS-CoV-2 Omicron BA.1 and BA.2 Infections - Medits, Iris; Springer, David N.; Graninger, Marianne; Camp, Jeremy V.; Höltl, Eva; Aberle, Stephan W.; Traugott, Marianna T.; Hoepler, Wolfgang; Deutsch, Josef; Lammel, Oliver; Borsodi, Christian; Puchhammer-Stöckl, Elisabeth; et al. (Frontiers in Immunology, 2022)
Background and Methods The SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) Omicron (B.1.1.529) variant is the antigenically most distinct variant to date. As the heavily mutated spike protein enables neutralization escape, we studied serum-neutralizing activities of naïve and vaccinated individuals after Omicron BA.1 or BA.2 sub-lineage infections in live virus neutralization tests with Omicron BA.1, Omicron BA.2, wildtype (WT, B1.1), and Delta (B.1.617.2) strains. Serum samples obtained after WT infections and three-dose mRNA vaccinations with and without prior infection were included as controls. Results Primary BA.1 infections yielded reduced neutralizing antibody levels against WT, Delta, and Omicron BA.2, while samples from BA.2-infected individuals showed almost no cross-neutralization against the other variants. Serum neutralization of Omicron BA.1 and BA.2 variants was detectable after three-dose mRNA vaccinations, but with reduced titers. Vaccination-breakthrough infections with either Omicron BA.1 or BA.2, however, generated equal cross-neutralizing antibody levels against all SARS-CoV-2 variants tested. Conclusions Our study demonstrates that although Omicron variants are able to enhance cross-neutralizing antibody levels in pre-immune individuals, primary infections with BA.1 or BA.2 induced mostly variant-specific neutralizing antibodies, emphasizing the differently shaped humoral immunity induced by the two Omicron variants. These data thus contribute substantially to the understanding of antibody responses induced by primary Omicron infections or multiple exposures to different SARS-CoV-2 variants and are of particular importance for developing vaccination strategies in the light of future emerging variants.